Analisis Kesalahan dalam Menyelesaikan Soal Cerita Materi Peluang Ditinjau dari Gaya Belajar Siswa di SMPN 7 Mataram - Sinta Silviana Muslim; Sudi Prayitno; Nilza Humaira Salsabila; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the types of errors of students who have visual, auditory, and kinesthetic learning styles in solving story problems of opportunity material. Error analysis was carried out based on the Newman procedure. The type of research used is descriptive qualitative research. The subjects of this study were students of class IX-A SMP Negeri 7 Mataram in the academic year 2021/2022 who were selected using a purposive sampling technique, then 2 students were selected from each type of learning style. Data collection techniques used are learning style questionnaires, story test questions, and interview guidelines. Based on the research results, it is known that 18 students have a visual learning style, 10 students have an auditory learning style and 2 students have a kinesthetic learning style. The data obtained from the research are: (i) students with visual learning styles tend to make transformation and encoding errors, (ii) students with auditory learning styles tend to make comprehension, transformation, process skill, and encoding errors, and (iii) students with kinesthetic learning styles tend to make comprehension, transformation, process skill, an encoding error. Although at first glance it looks the same, there are differences in the errors of students with auditory learning styles and students with kinesthetic learning styles, where in the process skill error of students with auditory learning styles are wrong in the calculation process while students with kinesthetic learning styles do not perform calculations to completion (jammed).